Political competition and economic policy: Empirical evidence from Pakistan - Ahmed Chaudhry; Ummad Mazhar (Economics: The Open-Access, Open-Assessment E-Journal, 2019)
The influence of politics on economic policy is not fully understood. The challenge to ensure political inclusiveness and economic prosperity remains. Perhaps, one way to attain this objective is by increasing political competition. This paper gathers empirical evidence from Pakistan, a country with a checkered political history characterized by episodes of representative, non-representative, and indirectly elected governments. In recent years, the country has witnessed a gradual strengthening of democratic rules with economic progress. Focusing on nine elections held over 1970 to 2015 the authors measure political competition and estimate its impact on economic policy. Contrary to popular conceptions about Pakistan's economy, they find a positive association between lack of political competition and poor economic policy. This finding holds at national as well as subnational levels in Pakistan and withstands a number of robustness tests.
http://dx.doi.org/10.7910/DVN/03SDLZ
Keywords: H21; H24; H31; J22; 330; political competition; Pakistan; economic policy; economic performance; subnational